The Effect of Differences in Concentration and Immersion Duration in Noni Extract to Expired Chili Seeds Viability - Trisda - Kurniawan (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2023)
Study in noni extract still limited to its capability to control a number of pests and pathogens, even though its also has antioxidant which potentially benefits in seed invigoration The objectives of this research was to determine the best noni extract concentration and the soaking duration, for expired chili seed invigoration. Research units arrangement and statistical analysis were according to factorial completely randomized design 5x3 with 3 replication. Factors being observed were noni extract concentrations (0%, 20%, 40%, 60%, and 80%) and soaking duration in non i extract (2 hours, 4 hours and 6 hours). The result showed that the best combination to invigorate expired chili seed was 20% in concentration for 2 hours of soaking duration.